Pembinaan Sistem Perbenihan Terpadu: Kasus Komoditas Kedelai - Masdjidin Siregar (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 1999)
EnglishThe availability of good quality seeds as the basis for good production is still a problem. The major objective of this paper is to describe formal and informal soybean seed systems in Indonesia. While the use of such national soybean varieties as Wilis, Galunggung, etc., has been relatively high (more than 70%), most soybean farmers obtain soybean seed from informal Jabalsim system that produces unlabelled or uncertified seeds. The system is but an inter-field and inter-seasonal seed flow through market in a region. The Jabalsim system is deemed adequate for farmers who have preference for fresh, cheap and timely available seed. Integration of formal system and Jabalsim system is therefore urgently needed. The Government (Office of Agricultural Services, Seed Control and Certification Station or BPSB) may increase the service to assist and train seed growers and middlemen involved in seed business. Good quality soybean seeds should be periodically injected to Jabalsim system. It is suggested that to improve the national seed system in general, the members of the National Seed Agency (BBN) should include various experts (in breeding, seed technology, and biotechnology fields) and private companies dealing with seed production and marketing. IndonesianKetersediaan benih bermutu sebagai dasar peningkatan produksi masih merupakan masalah. Makalah ini bertujuan untuk menggambarkan sistem perbenihan kedelai formal dan informal. Sementara tingkat penggunaan benih unggul nasional seperti Wilis, Galunggung dan sebagainya sudah relatif tinggi (lebih dari 70 persen), namun kebanyakan petani memperoleh benih kedelai dari sistem Jabalsim yang menghasilkan benih tidak berlabel. Sistem Jabalsim dipandang cukup memadai untuk para petani yang memiliki pilihan terhadap benih segar, murah dan tersedia manakala diperlukan. Karena itu maka integrasi sistem benih formal dan sistem informal sangat diperlukan. Dinas Pertanian dan Balai Pengawasan dan Sertifikasi Benih (BSPB) dapat meningkatkan pelayanannya untuk melaksanakan pelatihan bagi para penangkar benih dan pedagang benih. Benih Pokok (SS) bermutu perlu diinjeksikan secara berkala ke dalam sistem Jabalsim. Anggota Badan Perbenihan Nasional seharusnya terdiri dari berbagai tenaga ahli (pemuliaan tanaman, teknologi benih dan bioteknologi) dan perusahaan yang bergerak dalam produksi dan pemasaran benih.